Hubungan Kecerdasan Emosional(EQ) Dan Kecerdasan Spiritual(SQ) terhadap Hasil Belajar Peserta Didik - Engla islami; Ardi (Universitas Muhammadiyah Surabaya, 2025)
MAN 1 Pesisir Selatan is one of the aliyah madrasahs in the southern coastal area. The biology learning outcomes of students at MAN 1 Pesisir Selatan can be said to be low and also the level of emotional intelligence (EQ) and spiritual intelligence (SQ) is in the low category. The aim of this research is to determine the relationship between emotional intelligence (EQ) and spiritual intelligence (SQ) on the learning outcomes of MAN 1 Pesisir Selatan students. expost facto The sample in this research was 152 people. The sampling technique in this research is the Clustor Sampling (Area Sampling) technique. The data collection technique in this research was a Likert scale questionnaire with 5 answer choices and biology questions. To analyze the data, both descriptive and inferential statistics were used. To test the hypothesis, a multiple linear regression analysis model is used. The results of this research are that the variable is 0.911 and the correlation coefficient value is 0.917. The conclusion of this research is that there is a positive relationship between emotional intelligence (EQ) and spiritual intelligence (SQ) on student learning outcomes.